Whether sperm deoxyribonucleic acid fragmentation has an effect on pregnancy and miscarriage after in vitro fertilization/intracytoplasmic sperm injection: a systematic review and meta-analysis - Zhao, Jing; Zhang, Qiong; Wang, Yonggang; Li, Yanping (Fertility and sterility, 2014)
To examine whether sperm DNA fragmentation has an effect on pregnancy and miscarriage after IVF and/or intracytoplasmic sperm injection (ICSI). Systematic review and meta-analysis. University-affiliated teaching hospital. Infertility patient(s). An exhaustive electronic literature search was conducted on MEDLINE, Google Scholar, and the Cochrane Library, from database inception to October 2013. We included clinical trials that examined the influence of sperm DNA damage on pregnancy and miscarriage of IVF/ICSI. The outcomes of interest were pregnancy rate and miscarriage rate. In the analysis of pregnancy, 16 cohort studies (3,106 couples) were included. Of these, 14 studies (2,756 couples, 965 pregnancies) that also mentioned miscarriage were identified in the analysis of miscarriage. Meta-analysis showed that high-level sperm DNA fragmentation has a detrimental effect on outcome of IVF/ICSI, with decreased pregnancy rate and increased miscarriage rate. The stratified analysis by type of procedure (IVF vs. ICSI) indicated that high sperm DNA damage was related to lower pregnancy rates in IVF but not in ICSI cycles, whereas it was associated with higher miscarriage rates in both IVF and ICSI cycles. The results indicate that assays detecting sperm DNA damage should be recommended to those suffering from recurrent failure to achieve pregnancy. Selection of sperm without DNA damage for use may improve the clinical outcome of ART. The data also provide a rationale for conducting further research aimed at evaluating the underlying mechanism(s) responsible for the detrimental effect of high sperm DNA fragmentation and the potential therapy.